Analysis of E-Government-Based Public Service Quality and Public Satisfaction - Yosaphat Danis Murtiharso; Tomi Apra Santosa; Sunardi Sunardi; Mulyadi Mulyadi; Aat Ruchiat Nugraha (Citra Media Publishing, 2026)
Digital transformation in the public sector has prompted governments to implement e-government as a strategy to enhance the quality of public services, making them more effective, efficient, transparent, and responsive to public needs. Despite the development of various digital service innovations, public satisfaction levels regarding e-government services vary, influenced by factors such as system quality, information quality, service quality, ease of use, and the responsiveness of government personnel. This study aims to analyze the impact of e-government-based public service quality on public satisfaction. A quantitative approach with an explanatory research design was employed. Data were collected via questionnaires distributed to 250 respondents - users of e-government public services across several local government agencies - using proportionate random sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess construct validity and reliability, as well as causal relationships between variables. The results indicate that e-government-based public service quality has a positive and significant effect on public satisfaction (0.742; p < 0.001). Service quality dimensions - comprising ease of access, system reliability, service speed, information security, transparency, and personnel responsiveness - were found to contribute significantly to increased public satisfaction. These findings suggest that optimizing e-government implementation not only improves administrative efficiency but also strengthens public trust in public institutions through the provision of high-quality services.